Smart door using Kinect sensor - Mokhtar, Ammar Hazim; Mohd Ijazi, Badrul Hisham Fitri (2016)
This project is designed to detect the human body and open the door when a person is standing in front of the Kinect sensor. Apart from that, the hidden aim in this project is to able to configure the Kinect sensor using the MATLAB software and understand the command used in this project. Moreover, the project wishes to obtain specific data from the Kinect sensor and use the obtained data to send them over to the Arduino board in this project. After receiving the data, the Arduino will then run the desired program and run the servo motor connected to the pin 9 of the Arduino. The Kinect sensor is configured using a series of command in the MATLAB software such as initializing certain variables to activate the Kinect sensor. The data is then obtained in terms of “Metadata”. The “Metadata” is then used to initialize the connection between Arduino and MATLAB software. After the Arduino has received the “Metadata”, the Arduino will run the servo motor and open the door.